Women's Witnesses in the Resurrection of Jesus and Implications in Church Service - Ayub Sugiharto; Junio Richson Sirait (Jurnal Teologi (JUTEOLOG), 2022)
It is undeniable that women have been involved in the ministry, although their involvement is often debated to date. There are various reasons used to justify the group that disagrees, but also many arguments are given to support the involvement of women in services. This paper seeks to raise the role of women in the ministry of the church based on the New Testament. Hopefully this research is to clarify the understanding of Christians on the role of women in church services. In the midst of the struggles related to the position and dignity of women at that time, the New Testament records the involvement and role of women that cannot be taken lightly in the ministry. This can be seen from the Bible, how women were involved in the time of the Lord Jesus, the Acts of the Apostles which records the role of women in church ministry accompanying the apostles; as well as in Paul's letters where not a few women were partners with the Apostle Paul in the ministry.